Propuesta para actualizar los contenidos curriculares de un curso universitario impartido en la Facultad de Odontología, Universidad de Costa Rica - Sánchez-Achío, Tony (2021)
Objective. To carry out an update of the curricular contents for the program of the course of the degree in dentistry: Facial growth and development of occlusion, taught by the Department of Pediatric Dentistry and Orthodontics, University of Costa Rica, for the year 2019. Methods. The curricular programs of the Facial Growth and Occlusion Development course from 2014 to 2018 were taught by the Faculty of Dentistry of the University of Costa Rica; likewise the Dental Degree programs of the private universities that teach this degree. Subsequently, a list was made with all the other regents in the subject and a survey was conducted of specialists in the field, to define the importance of teaching them in the course studied. Results. Based on the data obtained by the opinions of the teachers, the importance of the topics to be integrated in the curriculum of the facial growth and occlusion development course will be listed in descending order. Conclusion. An educational proposal is achieved to update the curricular contents of a university course, eliminating the subjectivity of a single teacher. This type of consensus is necessary to satisfy the current needs and demands of the future professionals in this area.